PENGARUH KAPASITAS SUMBER DAYA MANUSIA, PERENCANAAN ANGGARAN, DAN POLITIK PENGANGGARAN,TERHADAP SINKRONISASI DOKUMEN APBD DENGAN DOKUMEN KUA-PPAS: TRANSPARANSI PUBLIK SEBAGAI VARIABEL MODERATING (Studi pada Pemerintah Kabupaten Bengkalis) - Elisabet Simanungkalit; Vince Ratnawati; Susilatri ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The Purpose of this study is to examine the influence of the capacity of human resources budget planning and budgeting politics on the synchronization between APBD and KUA-PPAS document. To examine moderate role of public transparency on the relationship between the capacity of human resources, budget planning, budgeting politics on the synchronization between APBD and KUA-PPAS document. The Sample of this study is employee on SKPD and we use purposive sampling method as sampling technique. The data was analy zed using multiple linier regression analysis. The Result shows that capacity of human resources, budget planning, political budgeting effect the synchronization between APBD and KUA-PPAS. The Result also shows the Capacity of Human Resources, Budget Planning and Budgeting Politics positive effect on the budget document synchronization on KUA-PPAS. However this study also show that Public transparency moderates the effect of Human resource capacity on synchronization between APBD and KUA-PPAS document. Contrary, this study shows that budgeting politic does not moderate the effect of synchronization between APBD on KUA-PPAS document.Keywords : Synchronization, Human Resource Capacity, Budget Planning, Budgeting Politics, and Public Transparency